Productivity - Haynes, Michael, 1951- (Economy, key ideas., 2020)
Since the 2008 financial crisis, the UK's productivity has fallen dramatically and now lags behind that of other European countries, most notably Germany. For this reason, the word "productivity" looms large in public policy discussions and has become the focus of complex debate. However, many find themselves hard-pressed to explain exactly what the term means. Mike Haynes provides a detailed examination of the concept, how it is used, and why it is held by economists to be so important in evaluating the health of modern economies. Haynes maintains that too little attention is paid to why productivity grows or fails to grow in certain contexts as well as the difficulties involved in measuring its scope. Using a range of case studies to illustrate his points, Haynes examines how real world variables such as social welfare, automation and the reorganization of global and local economies interact with measurements of efficiency and output. Further, the book explores the competition in productivity between economically advanced countries in North America and Europe as well as uneven growth in less powerful economies. The book concludes by discussing whether growth in productivity is sustainable or whether productivity is, in fact, no longer the motor of economic growth that it once was and no longer the most appropriate economic indicator for modern economies.